High level of phenotypic homoplasy amongst eutardigrades (Tardigrada) based on morphological and total evidence phylogenetic analyses. (29th August 2013) - Guil, Noemi; Machordom, Annie; Guidetti, Roberto
Abstract : Much of what is known about the phylogenetic relationships of the neglected phylum Tardigrada comes from molecular data, rather than from morphology‐based phylogenetic studies. Several molecular phylogenies have been proposed, but morphological and total evidence phylogenetic approaches are scarce. We performed the first morphological phylogeny (based on maximum parsimony and Bayesian inference) including all genera from the class Eutardigrada. Furthermore, we carried out a total evidence approach adding molecular information available in public databases. We compared the morphological and total evidence phylogenies with current molecular hypotheses and Eutardigrada classifications, which our results partially support. These classifications were supported only when homoplastic characters (related to the buccopharyngeal apparatus) were excluded. The importance of morphological phylogenies is discussed as well as their utility for questioning current phylogenetic hypotheses and classifications based solely on molecular information. Lastly, we propose evolutionary hypotheses about eutardigrade phylogenetic relationships that should be tested based on our morphological results. © 2013 The Linnean Society of London